SentraGakkumdu Challenges in Enforcing Election Crimes Under Law Number 7 of 2017: A Comparative Research of Indonesia and Nigeria - Angela, Deni (Ius Poenale, 2024)
General elections in Indonesia are designed to ensure equality and justice for all voters and candidates, regardless of party affiliation. Despite these principles, election violations do occur, including criminal acts, breaches of ethical standards by election organizers, and administrative violations related to election procedures. To protect the integrity of elections, which is crucial for democracy, lawmakers have classified certain electoral frauds as criminal offenses. The Election Law not only outlines the procedures for conducting elections but also prohibits actions that undermine the fairness of the process and imposes penalties on offenders. The type of research in this study is normative legal research, which is a research method that focuses on written legal norms. accompanied by a comparative study of the country of Nigeria The results showed that the small number of reports of election crimes that continued to the level of investigation, prosecution, and examination in court until the issuance of a permanent legal force decision (inkracht van gewisjde) showed that the handling of election crimes in the elections had not been effective. The same is true for Nigeria through INEC. Although INEC has the authority to initiate cases of electoral offenses, it rarely does so due to a lack of supervisory capacity due to understaffing and the inability or unwillingness of the police to collect evidence and conduct investigations.